Book Review - Bernstein, Marc D. (Columbia Journal of Environmental Law, 2020)
REGULATION AND THE COURTS: THE CASE OF THE CLEAN AIR ACT. By R. Shep Melnick. Washington, D.C.: Brookings Institution,1983. Pp. x, 404. Cloth $29.95, Paper $11.95.